Associations between self-perceived voice disorders in teachers, perceptual assessment by speech-language pathologists, and instrumental analysis (2016)
Purpose: The three aims of this study were to assess agreement between self-perceived voice disorders, perceptual and instrumental assessment; to determine factors associated with perceptual voice assessment; and to determine which associated factors would serve as an initial screening tool for ascertainment of the presence or absence of voice disorders among teachers. Method: A cross-sectional study was conducted among 574 Colombian teachers. Participants filled in a questionnaire and recorded a voice sample. The voice samples were perceptually evaluated by a speech-language pathologist with the Grade, Roughness, Breathiness, Asthenia, and Strain (GRBAS) scale and objectively with an automated voice analysis for fundamental frequency, jitter, shimmer and maximum phonation time. Agreements between GRBAS scale, self-reported voice disorders and instrumental analysis were determined by unweighted Cohe?s Kappa coefficients and receiver operating characteristic curves. Multivariate logistic regression analysis was used to identify variables associated with the perceptual assessment. Diagnostic performance of these variables was assessed by the area under the curve. Result: There was no agreement between self-reported voice disorders and GRBAS assessments. Maximum phonation time showed a slight agreement with perceptual assessment of voice disorders. Conclusion: Since these three methods offer different information, it is advisable to include all methods in ascertainment of voice disorders among teachers at work. © 2016 The Speech Pathology Association of Australia Limited Published by Taylor and Francis.